Parents' satisfaction with their children's dental care provided by the paediatric polyclinic, Kulliyyah of Dentistry, International Islamic University Malaysia - Muhannad Kashmoola, Sayfaldeen; Ghazali, Ahmad Badruddin; Harun, Nor Asilah; Abu Kassim, Noor Lide (2014)
Patient satisfaction is the perception of the patient toward services provided as a whole (procedures and outcomes ), which might be positive or negative. It is an important tool for assessing quality in dental care. In pediatric dental care, patient satisfaction would be evaluated more effectively through parents’ perception as pediatric patients are sometimes too young to express their perception accurately.